STAG2 deficiency induces interferon responses via cGAS-STING pathway and restricts virus infection - Siyuan Ding (Nature Portfolio, 2018)
Cohesin is a multimeric nuclear protein complex which includes STAG2 and is associated with vital roles during cell division. Here in a genome-wide CRISPR-Cas9 screen, the authors identify a novel role of STAG2 as a crucial component of the innate immune response to rotavirus.